Penerapan Strategi Manajemen Persediaan pada Produk UMKM Smoothies di Beberapa Gerai Kota Gorontalo dalam Menghadapi Turbulensi Lingkungan Bisnis - Valentina Monoarfa; Pratiwi Setyanti; Vitta Aliska Katili (ManBiz: Journal of Management and Business, 2024)
UMKM Smoothies are drinks that are currently popular. Drinks are made from a mixture of fruit and are usually added with additional yogurt, vegetable milk, or other fruit juice. Smoothies are often considered a healthy drink choice because they contain quite high nutritional content, such as fiber and vitamins. Apart from that, smoothies can also help increase energy and improve the digestive system. The tradition of drinking smoothies has existed in various cultures and has become a healthy drink trend in all circles. However, Smoothies UMKM have not implemented inventory management in managing the best raw materials. This research was conducted with the aim of finding out what kind of efforts they make in managing raw materials, and how the sales of UMKM Smoothies products face the turbulence of the business environment. Data collection in this research was carried out through interviews, observation and documentation